2020
DOI: 10.1109/access.2020.3009439
|View full text |Cite
|
Sign up to set email alerts
|

Similarity-Based Machine Learning Model for Predicting the Metabolic Pathways of Compounds

Abstract: Metabolic pathways refer to the continuous chemical reactions in the metabolic process in vivo. Compounds are the major participant for most metabolic pathways. It is essential to determine which compounds can constitute a metabolic pathway. This problem can be converted to the identification of the metabolic pathways of compounds. Although traditional experiments can provide solid results, they are always of low efficiency and high cost. To date, several machine leaning models have been proposed to address th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…In fact, we also tried SVM (RBF kernel) and random forest (RF) [ 43 ]. Like SVM, RF is also a widely used and powerful classification algorithm [ 8 , 11 , 22 , 44 47 ]. For SVM (RBF kernel), the same values of regularization parameter C were tried, and γ was set to 0.01, 0.02, and 0.03.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, we also tried SVM (RBF kernel) and random forest (RF) [ 43 ]. Like SVM, RF is also a widely used and powerful classification algorithm [ 8 , 11 , 22 , 44 47 ]. For SVM (RBF kernel), the same values of regularization parameter C were tried, and γ was set to 0.01, 0.02, and 0.03.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the multilabel classification problem was transformed into a binary classification problem. Jia et al [ 11 ] extended the above model to an actual metabolic pathway rather than a pathway type. The concept of “similarity” was adopted to extract essential features for each pair of chemical and pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Random forest is widely adopted in the investigation of biological and biomedical data ( Pan et al, 2010 ; Zhao et al, 2018 ; Chen et al, 2019 ; Jia et al, 2020 ; Liang et al, 2020 ), and it has shown satisfactory performance in numerous studies. As a meta classifier, RF consists of multiple DTs, where each DT is learned from a bootstrap sample set with a randomly selected feature subset.…”
Section: Methodsmentioning
confidence: 99%
“…The RF ( Breiman, 2001 ; Wei et al, 2017 ; Zhao et al, 2018 ; Baranwal et al, 2019 ; Jia et al, 2020 ; Liang et al, 2020 ) is a tree-based assembly model that predicts the class label of a new sample on the basis of the consensus results of the average predictions from multiple decision trees (DTs). In the present study, we used the RF implemented in the Scikit-learn package.…”
Section: Methodsmentioning
confidence: 99%